2014
DOI: 10.1037/a0037127
|View full text |Cite
|
Sign up to set email alerts
|

Unfinished tasks foster rumination and impair sleeping—Particularly if leaders have high performance expectations.

Abstract: This study examines the relationship between time pressure and unfinished tasks as work stressors on employee well-being. Relatively little is known about the effect of unfinished tasks on well-being. Specifically, excluding the impact of time pressure, we examined whether the feeling of not having finished the week's tasks fosters perseverative cognitions and impairs sleep. Additionally, we proposed that leader performance expectations moderate these relationships. In more detail, we expected the detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 60 publications
8
130
0
Order By: Relevance
“…Conceivably, the adverse effects of role ambiguity might result in stronger negative affective states during work time or directly after work but might be less salient before bedtime. By contrast, in accordance with the Zeigarnik effect, unfinished tasks might trigger work‐related rumination (Berset, Elfering, Lüthy, Lüthi, & Semmer, ; Syrek & Antoni, ) and hence maintain a state of high negative activation or tense arousal and irritation—consequently impairing recovery processes. This finding contributes to the recently suggested concept of the “recovery paradox” (Sonnentag, ).…”
Section: Discussionmentioning
confidence: 96%
“…Conceivably, the adverse effects of role ambiguity might result in stronger negative affective states during work time or directly after work but might be less salient before bedtime. By contrast, in accordance with the Zeigarnik effect, unfinished tasks might trigger work‐related rumination (Berset, Elfering, Lüthy, Lüthi, & Semmer, ; Syrek & Antoni, ) and hence maintain a state of high negative activation or tense arousal and irritation—consequently impairing recovery processes. This finding contributes to the recently suggested concept of the “recovery paradox” (Sonnentag, ).…”
Section: Discussionmentioning
confidence: 96%
“…Second, when being online and after having been interrupted by an online message, a high responsiveness should be encouraged. Because leaving tasks unfinished can have undesirable consequences (Syrek & Antoni, ; Zeigarnik, ), it seems particularly important that employees do not only read incoming online messages, but that they decide quickly if an answer is needed, how they will respond to each specific message, and actually prepare the answer. Immediately focusing on incoming e‐mails, however, postpones work on other tasks, potentially leading to switching costs with respect to other duties.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas our study was focused on how sleep quality is related to procrastination the following workday, procrastination at work, in turn, might diminish employees' subsequent sleep. Postponing the completion of activities at work may result in unfinished tasks weighing heavily on one's mind during off‐job time, potentially threatening recovery during non‐work activities (Sonnentag & Fritz, ) as well as one's sleep (Syrek & Antoni, ). Additional analyses in our dataset showed that day‐specific procrastination at work was not a significant predictor of sleep quality the following night.…”
Section: Discussionmentioning
confidence: 99%